Comparative study on different therapies on patients with primary central nervous system lymphoma - Xuchu Yang (Saudi Journal of Biological Sciences, 2019)
Objective: To compare and analyze three therapies on patients with primary central nervous system lymphoma (PCNSL), aiming to provide evidences for future treatment and prognosis. Methods: Clinical data of 26 cases of PCNSL with normal immune system confirmed by postoperative pathology were retrospectively analyzed. Among them there were six cases with operation only, nine cases with operation and radiotherapy, and 11 cases with operation, radiotherapy and chemotherapy, and their survival rate was compared as well. Results: The survival time of patients with operation only, operation combined with radiotherapy and operation combined with radiotherapy and chemotherapy was 6–11 months, 15–24 months and 24–51 months, respectively. And their median survival time was only nine months, 21 months and 38 months, respectively. Conclusions: Operation combined with radiotherapy and chemotherapy can dramatically extend PCNSL patients’ survival time, therefore, it can be regarded as the first-line therapy. Keywords: Primary central nervous system lymphoma, Surgical therapy, Radiotherapy, Chemotherapy